Feasibility of a Trans Central and East African Pipeline (An Economic Perspective) - Ihejirika, Vivian; Ogbonna, Joel; Ikiensikimama, Sunday (International Journal of Engineering Science Invention (IJESI), 2021)
Inadequate infrastructure has been the major hindrance preventing the projected growth of the Nigeria gas industry. Gas infrastructures are capital intensive, and has long pay-back time, hence the involvement of international financial backbone or strong government participation is essential when planning for infrastructural development in the industry. However, the Nigerian government has shown to lack the political will and economic knowledge needed to achieve sustainable and profitable infrastructural development. This paper therefore performed an economic analysis of a Trans Central and East Africa gas Pipeline infrastructure proposal. It outlines the benefit of the pipeline to Nigeria and Africa at large and also perform an economic analysis forecast using a cash flow state to determine the pipeline profitability. The Economic analysis forecasted at $35 billion capital investment gave a net cash flow of $17.2108 billion/year at peak performance, and a 7 years payback period. With a 20-year cash flow forecasted, the project was discounted at 10%, and 15%, and the NPV derived was $62,804.48 million and $55,482.42 respectively with an IRR of 28%. Furthermore, a sensitivity analysis was carried out to ascertain the project performance under certain conditions of 50%, 75% and 100% production rate to emulate worst, medium and best-case scenarios, the project still showed profitable at worst case scenario of 50%, with an NPV of 10% and 15% the cash flow calculated was $63,804.48 million and $55,482.42 million respectively and an IRR of 28%.
Keywords: Natural Gas; Gas Economics; Economic analysis; Gas infrastructure; Pipeline infrastructure